Recent Advances in Internet-Delivered, Evidence-Based Weight Control Programs for Adults - Krukowski, Rebecca A. (Diabetes Technology Society, 2009)
With the explosion of Internet accessibility, online delivery offers potential for significantly greater reach of evidence-based obesity treatment programs for adults. Online behavioral weight control has been shown to produce significant weight loss, with more recent programs demonstrating larger losses and general consumer satisfaction. A growing literature indicates several program parameters that may offer greatest engagement in online obesity interventions and better weight loss outcomes, including interactive, dynamic Web site features and synchronous counselor contact, although this research is in the early stages, and a clear picture of the essential components for the most effective online obesity program remains to be determined. Further research is required to enhance weight loss outcomes, determine cost-effectiveness of Internet-delivered programs, and identify the individuals most likely to benefit from treatment in this format.